Incidentally Detected Extensive Disseminated Cysticercosis in A Case of Nasopharyngeal Carcinoma: Life Sciences -Pathology - Wajpeyi, Dr. Ketki; Vagha, Dr. Sunita (International Journal of Life Science and Pharma Research, 2023)
Taenia solium, a pork tapeworm, causes a parasitic infection called cysticercosis. It is a frequent source of seizures and neurological morbidity in developing countries. An uncommon presentation of cysticercosis is neurocysticercosis, and till now, less than fifty cases have been noted in the world’s literature; most of the cases belong to India. In this study, we have reported an unusual patient of a nasopharyngeal carcinoma presenting with occasional epistaxis and progressively enlarging left submandibular swelling, who has later diagnosed to harbor coexistent disseminated cysticercosis involving multiple sites in the body, namely the brain, extraocular muscles, skeletal muscles, tongue, heart, pleura, peritoneum, aortic wall, seminal vesicles, and scrotal sac. Here we report a 60 years old male patient presenting with occasional nasal bleeding, a headache for 6 months, and swelling in the left submandibular region for 4 months. In the past, the patient had a history of seizure episodes. Nasal endoscopy revealed a mass in the roof of the nasal cavity. A biopsy confirmed the diagnosis of nasopharyngeal carcinoma.Further radiological investigations were made for staging when the patient was detected with extensive rice grain calcifications leading to an incidental diagnosis of disseminated cysticercosis. The first case we know of was detected on an FDG PET/CT (fluorodeoxyglucose-positron emission tomography/computed tomography) scan. The patient was managed with chemoradiotherapy for nasopharyngeal carcinoma and subsequently 400 milligrams of oral albendazole, twice daily, and 20 milligrams of prednisolone, twice daily for three weeks for disseminated cysticercosis. Prednisolone was eventually waned off and terminated. The patient’s condition had significantly improved at the 3-month follow-up, and no seizure recurrence was observed. This case report aims to depict the disease’s presentation, provide information on this globally prevailing pathogen, and shed some light on the infection’s diagnostic workup and therapeutic interventions.